Pengaruh Penerapan Sistem Akuntansi Keuangan Daerah, Kompetensi Aparatur Pemerintah, Pemanfaatan Teknologi Informasi dan Kapasitas Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan dengan Sistem Pengendalian Internal Sebagai Variabel Moderasi : (Organisasi Perangkat Daerah di Kota Kudus) - Durotul Khumairoh; Nafi’ Inayati Zahro; Dennyca Hendriyanto N (CV. Ulil Albab Corp, 2024)
The aim of this research is to test and analyze the influence of the implementation of a regional financial accounting system, the competence of government officials, the use of information technology and human resource capacity on the quality of financial reports with an internal control system as a moderating variable in regional apparatus organizations in Kudus City. The population in this study was all regional officials in Kudus City, while the sample in this study was 132 respondents who were selected using purposive sampling techniques. This research uses data analysis in the form of research instrument tests, descriptive statistical analysis and moderated regression analysis (MRA). Based on the research results, it was found that the implementation of regional financial accounting systems, the competence of government officials, the use of information technology and human resource capacity have a positive effect on the quality of financial reports. The internal control system is unable to moderate the influence of the implementation of regional financial accounting systems, the competence of government officials and human resource capacity on the quality of reports, while the internal control system is able to moderate the influence of the use of information technology on the quality of financial reports.